(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
This paper is concerned with the global exponential stability(GES) and stabilization of fractional-order positive switched systems(FOPSS) with average dwell time(ADT). Firstly, the the concept of GES is extended to FOPSS. Then, by constructing copositive Lyapunov functions and using ADT approach, a state feedback controller is constructed, and sufficient conditions are derived to guarantee that the corresponding closed-loop system is globally exponentially stable. Such conditions can be easily solved by linear programming. Finally, an example is given to demonstrate the effectiveness of the proposed method.